2011
DOI: 10.1037/a0021135
|View full text |Cite
|
Sign up to set email alerts
|

Sexual overperception: Power, mating motives, and biases in social judgment.

Abstract: Results from 4 experiments suggest that power motivates heightened perceptions and expectations of sexual interest from subordinates. Having power over a member of the opposite sex activated sexual concepts that persisted across a temporal delay, indicating the activation of a mating goal (Study 1). Having power increased participants' expectations of sexual interest from a subordinate (Study 2) but only when a mating goal was attainable (i.e., when the subordinate was romantically available; Study 3). In a fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
58
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 56 publications
(123 reference statements)
10
58
1
1
Order By: Relevance
“…Research has also examined situational moderators. For example, Kunstman and Maner showed that men and women who held powerful roles tended to overestimate sexual interest communicated by the opposite sex, consistent with evolutionary evidence that those atop the social hierarchy tend to enjoy greater access to potential mates [33]. Finally, men who were exposed to the scent of female ovulation overestimated women's level of sexual interest, consistent with the idea that ovulation can spark male mating motives [34].…”
Section: Underlying Theoretical Bases Of Mating-related Cognition Thesupporting
confidence: 54%
“…Research has also examined situational moderators. For example, Kunstman and Maner showed that men and women who held powerful roles tended to overestimate sexual interest communicated by the opposite sex, consistent with evolutionary evidence that those atop the social hierarchy tend to enjoy greater access to potential mates [33]. Finally, men who were exposed to the scent of female ovulation overestimated women's level of sexual interest, consistent with the idea that ovulation can spark male mating motives [34].…”
Section: Underlying Theoretical Bases Of Mating-related Cognition Thesupporting
confidence: 54%
“…Together with Gervais et al (2012) and Bernard et al, the results from Civile and Obhi contribute to a better understanding of the cognitive processes underpinning sexual objectification of both men and women. Moreover, these results along with some previous studies (Gruenfeld, Inesi, Magee, & Galinsky, 2008;Kunstman & Maner, 2011) suggest that priming individuals to highpower may activate a mating goal that could lead to objectification of others when presented within a sexualized context (Civile & Obhi, 2015).…”
Section: Social Power and Sexual Objectificationmentioning
confidence: 58%
“…(Depret & Fiske, 1993). In the case of sexual objectification, when individuals are primed to highpower, not only are they primed to seek out a potential mate (see Civile & Obhi, 2015;Kunstman & Maner, 2011) but are also more likely to rely on stereotypes in identifying a potential mate. It could be argued that the media has created stereotypes of Caucasian women and men that are more sexualized than stereotypes of their Asian counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…These regression weights were ß = .14 for men and ß = .12 for women-a small but significant difference-although no such sex difference emerged for ambition in this study (ß = .01 for both sexes). Other speed-dating studies failed to find a sex difference in the association of attractiveness with participants' decision to say "yes" to a speed-dating partner (Kurzban & Weeden, 2005) and with participants' romantic attraction to a partner (Luo & Zhang, 2009). Eastwick and Finkel (2008a) conducted a speed-dating study to examine the physical attractiveness and earning prospects sex differences in detail, and their 17 dependent measures of romantic interest were assessed both immediately after the speed date (e.g., romantic desire, romantic chemistry, the "yes" vs. "no" decision) and during the subsequent month (e.g., romantic passion, date initiation, date enjoyment).…”
Section: Predictive Validity Of Sex Differencesmentioning
confidence: 92%